An Empirical Investigation into the Impact of Social Media Fitness Videos on Users’ Exercise Intentions - He Yin; Xin Huang; Guangming Zhou (Behavioral Sciences, 2024)
Social media fitness influencers are driving the maturation of online fitness, which is especially significant in the current era of globally decreasing levels of physical activity. However, there is a paucity of research on online fitness videos, and the mechanism of influence of fitness videos on exercise intention is not well understood. Therefore, based on the stimulus–organism–response (S-O-R) theoretical framework, this study extends the source credibility theory to the field of fitness and adds an examination of the content quality and electronic word-of-mouth of fitness videos to explore how fitness videos motivate users to participate in physical exercise. Through an online survey, 367 valid samples were collected and validated using a structural equation model. The results showed that the three elements contained in source credibility theory have inconsistent importance in the fitness field, with trustworthiness being the most important, followed by attractiveness, and the influence of expertise is not significant. In summary, the attributes of social media fitness influencers, including trustworthiness and physical attractiveness, as well as the content quality and electronic word-of-mouth of their fitness videos, may lead to viewers’ trust and perception of the usefulness of the videos and, furthermore, lead to exercise intention.